Impact of Chrysanthemum fontanesii extract on sodium valproate mediated oxidative damage in mice kidney - Amel Amrani, Ouahiba Benaissa, Nassima Boubekri, Kenza Biod, Radja Djabari, Nawal Beroal, Djamila Zama, Fadila Benayache, Samir Benayache (Journal of Applied Pharmaceutical Science, 2016)
The objective of this study was to evaluate the potential of n-butanol extract obtained from flowers of Chrysanthemum fontanesii (Cf) and vitamin E against kidney oxidant injury induced by sodium valproate in mice. The evaluation was made through Histopathological examination and measuring kidney lipid peroxidation (LPO) and antioxidant parameters: reduced glutathione (GSH), glutathione peroxidase (GPx) and catalase. Severe alterations in all biomarkers were observed after injury with VPA. Treatment with Cf extract and vitamin E resulted in markedly decreased levels of LPO while increased levels of GSH and antioxidant enzymes activities were observed. In conclusion, n-butanol extract of Cf may be an interesting candidate for the treatment of kidney injury induced by VPA through enhancing endogenous antioxidant defenses and normalizing the kidney histopathological architecture.
Keywords: Valproic acid, Chrysanthemum fontanesii, kidney oxidant injury, Antioxidant, Renoprotective effect.